PENGEMBANGAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI SENAM DI SD AMIR HAMZAH - Sastri Dalila; Suyono; Ratika Balqis; Nur Hafni Siambaton (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Gross motor skills refer to exercises that involve the large muscles of the body. Gymnastics can help children's physical development, such as endurance and muscle strength. This research aims to find out how teachers can develop children's overall gross motor skills through gymnastics in elementary school. This research is descriptive qualitative research involving a teacher in the classroom. Data was collected through observation, interviews and document analysis. Data analysis was carried out qualitatively. The research results show that the teacher's efforts in developing children's gross motor skills are as follows; firstly invite the child to move, secondly correct wrong movements. These findings were discovered in research which can later be used to develop gross motor skills.